Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find matrix [tex]\(Y\)[/tex] given the equation [tex]\(X - 2Y = Z\)[/tex], we follow these steps:
1. Write down the matrices [tex]\(X\)[/tex], [tex]\(Y\)[/tex], and [tex]\(Z\)[/tex]:
[tex]\[ X = \begin{pmatrix} b & a \\ 4 & a \end{pmatrix}, Y = \begin{pmatrix} c & d \\ a & b \end{pmatrix}, Z = \begin{pmatrix} a & c \\ 16 & b \end{pmatrix} \][/tex]
2. Substitute these matrices into the equation [tex]\(X - 2Y = Z\)[/tex]:
[tex]\[ \begin{pmatrix} b & a \\ 4 & a \end{pmatrix} - 2 \begin{pmatrix} c & d \\ a & b \end{pmatrix} = \begin{pmatrix} a & c \\ 16 & b \end{pmatrix} \][/tex]
3. Multiply matrix [tex]\(Y\)[/tex] by 2:
[tex]\[ 2Y = 2 \begin{pmatrix} c & d \\ a & b \end{pmatrix} = \begin{pmatrix} 2c & 2d \\ 2a & 2b \end{pmatrix} \][/tex]
4. Subtract [tex]\(2Y\)[/tex] from [tex]\(X\)[/tex]:
[tex]\[ \begin{pmatrix} b & a \\ 4 & a \end{pmatrix} - \begin{pmatrix} 2c & 2d \\ 2a & 2b \end{pmatrix} = \begin{pmatrix} a & c \\ 16 & b \end{pmatrix} \][/tex]
5. Calculate the elements of the resulting matrix:
- For the first element [tex]\((1,1)\)[/tex], we have [tex]\(b - 2c = a\)[/tex]. Thus, [tex]\(2c = b - a\)[/tex].
- For the second element [tex]\((1,2)\)[/tex], we have [tex]\(a - 2d = c\)[/tex]. Thus, [tex]\(2d = a - c\)[/tex].
- For the third element [tex]\((2,1)\)[/tex], we have [tex]\(4 - 2a = 16\)[/tex]. Thus, [tex]\(2a = 4 - 16 = -12\)[/tex] and [tex]\(a = -6\)[/tex].
- For the fourth element [tex]\((2,2)\)[/tex], we have [tex]\(a - 2b = b\)[/tex]. Thus, [tex]\(2b = a - b\)[/tex].
Since we need the elements of matrix [tex]\(Y\)[/tex]:
- [tex]\(c = \frac{b - a}{2}\)[/tex]
- [tex]\(d = \frac{a - c}{2}\)[/tex]
- [tex]\(a = -6\)[/tex]
- [tex]\(b = x\)[/tex] (undetermined in the provided information)
After simplifying:
- Let’s use specific values to solve further since the equation can be ambiguous with undetermined variables. From further simplification, there can be specific solutions for distinct [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
Given correct calculations:
[tex]\[ Y = \begin{pmatrix} \text{(relate c to b and a specific value )} & \text{new d (solved constant) } \\ -6 & \text{ solved b content }\end{pmatrix} \][/tex]
1. Write down the matrices [tex]\(X\)[/tex], [tex]\(Y\)[/tex], and [tex]\(Z\)[/tex]:
[tex]\[ X = \begin{pmatrix} b & a \\ 4 & a \end{pmatrix}, Y = \begin{pmatrix} c & d \\ a & b \end{pmatrix}, Z = \begin{pmatrix} a & c \\ 16 & b \end{pmatrix} \][/tex]
2. Substitute these matrices into the equation [tex]\(X - 2Y = Z\)[/tex]:
[tex]\[ \begin{pmatrix} b & a \\ 4 & a \end{pmatrix} - 2 \begin{pmatrix} c & d \\ a & b \end{pmatrix} = \begin{pmatrix} a & c \\ 16 & b \end{pmatrix} \][/tex]
3. Multiply matrix [tex]\(Y\)[/tex] by 2:
[tex]\[ 2Y = 2 \begin{pmatrix} c & d \\ a & b \end{pmatrix} = \begin{pmatrix} 2c & 2d \\ 2a & 2b \end{pmatrix} \][/tex]
4. Subtract [tex]\(2Y\)[/tex] from [tex]\(X\)[/tex]:
[tex]\[ \begin{pmatrix} b & a \\ 4 & a \end{pmatrix} - \begin{pmatrix} 2c & 2d \\ 2a & 2b \end{pmatrix} = \begin{pmatrix} a & c \\ 16 & b \end{pmatrix} \][/tex]
5. Calculate the elements of the resulting matrix:
- For the first element [tex]\((1,1)\)[/tex], we have [tex]\(b - 2c = a\)[/tex]. Thus, [tex]\(2c = b - a\)[/tex].
- For the second element [tex]\((1,2)\)[/tex], we have [tex]\(a - 2d = c\)[/tex]. Thus, [tex]\(2d = a - c\)[/tex].
- For the third element [tex]\((2,1)\)[/tex], we have [tex]\(4 - 2a = 16\)[/tex]. Thus, [tex]\(2a = 4 - 16 = -12\)[/tex] and [tex]\(a = -6\)[/tex].
- For the fourth element [tex]\((2,2)\)[/tex], we have [tex]\(a - 2b = b\)[/tex]. Thus, [tex]\(2b = a - b\)[/tex].
Since we need the elements of matrix [tex]\(Y\)[/tex]:
- [tex]\(c = \frac{b - a}{2}\)[/tex]
- [tex]\(d = \frac{a - c}{2}\)[/tex]
- [tex]\(a = -6\)[/tex]
- [tex]\(b = x\)[/tex] (undetermined in the provided information)
After simplifying:
- Let’s use specific values to solve further since the equation can be ambiguous with undetermined variables. From further simplification, there can be specific solutions for distinct [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
Given correct calculations:
[tex]\[ Y = \begin{pmatrix} \text{(relate c to b and a specific value )} & \text{new d (solved constant) } \\ -6 & \text{ solved b content }\end{pmatrix} \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.